Women’s entrepreneurship and the future of the veterinary profession - Henry, C.; Jackson, Elizabeth (2015)
The veterinary profession, once traditional and predominately male, is becoming increasingly feminized, with women now making up some 80% of the veterinary student population, and over half the veterinary workforce. Given the fact that there are significantly fewer female than male business owners and entrepreneurs globally, across all sectors, there are growing fears that women will not come forward to take on the veterinary business and entrepreneurial leadership roles previously filled by men. This raises concerns in relation to the future of the profession as a whole. In this article we discuss some of the reasons behind the current gender disparity in veterinary business and entrepreneurial leadership roles, and suggest some potential solutions. Specifically, we highlight the role of veterinary schools in shaping the female veterinary business and entrepreneurial leaders of the future.